Transformasi Pembelajaran Melalui Penggunaan Multimedia Interaktif Berbasis Game: Persepsi Guru di Sekolah Dasar - Saputri, Dwi Yuniasih; Rukayah, Rukayah; Indriayu, Mintasih (Jurnal Pancar, 2018)
This study aims to describe: (1) teacher acceptance of game-based interactive multimedia as a learning medium; (2) teacher's understanding of game-based interactive multimedia; and (3) teacher assessment of game-based interactive multimedia. The research method used is descriptive qualitative. Data collection is done using the method of observation and interviews. Data analysis techniques used are interactive analysis consisting of data collection, data reduction, data presentation and conclusion drawing. The results of this study indicate that (1) teachers provide good acceptance of game-based interactive multimedia because learning becomes more active and student-centered; (2) interactive multimedia based on simple games so that it is easy to use to help students learn; and (3) the teacher has a good assessment of game-based interactive multimedia so that it can be used as a companion learning media both at school and at home